Τhe role of the diabetes clinical nurse specialist in the education of diabetic children - Charalambous, Andreas (My University, 2006)
Diabetes mellitus as a dangerous plague of this century and the value of the education of the diabetic child in the decrease of its complications have led to the development of the notion of the diabetes clinical nurse specialist in educating the diabetic children and their families. This article analyses the potential positive outcomes of the diabetes clinical nurse specialist in the education of the diabetic children and their families for improving the control of diabetes and increasing their ability for self care as these are evident by the current literature. The clinical nurse specialist in the paediatric clinics can be a significant institution which can be of great help in the formation of substantial curative relationships with the diabetic children and their families. However, the successful introduction of change in the clinical setting requires specific knowledge about the process of change.
Keywords: Diabetes clinical nurse specialists; Diabetes mellitus; Process of change; Teaching program